JENIS–JENIS ANAK POHON DI GUNUNG KELUD JAWA TIMUR - Inge Larashati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Mount Kelud is one of the active volcanic mountain harmless located in East Java with a height of 1731 meters above sea level. Kelud Peak, Gajah Mungkur Peak, Sumbing Peak, and Gedang Peak. Forests in mountain Kelud regions classified as lowland rain forest types with a bumpy terrain and very steep hill. Although the forest was damaged but Kelud has a very important function, considering in this area, there are numbers of upstream tributaries which serve as hidroorologis in East Java Province. Therefore, the presence of vegetation in the forest Kelud important to know by doing the analysis. The study of sapling height size more than 1.5 meters and trunk diameter of less than 10 cm is done by using square plots method. The results showed that the sapling species that dominate the region include: Dendrocalamus asper, Evodia glabra, Dendrocnide stimulans, Lithocarpus sundaicus, Ostodes paniculata and Leea indica.